2000
DOI: 10.1021/jp9937095
|View full text |Cite
|
Sign up to set email alerts
|

Femtochemistry of Hydrogen Bonded Complexes after Electronic Excitation in the Liquid Phase:  The Case of Coumarin 102

Abstract: We review our results on hydrogen bonding dynamics in the electronically excited state of coumarin 102 (C102), where we deduced that a hydrogen bond cleavage occurs within 200 fs. We compare the electronic absorption and emission properties of C102 hydrogen bonded to CHCl3, phenol or 2,2-dimethyl-3-ethyl-3-pentanol. We introduce the technique of two-pulse photon echo to show that an optical coherence between the optically coupled electronic ground and excited states survives until 180−200 fs, in the case of C1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
95
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(108 citation statements)
references
References 94 publications
8
95
1
Order By: Relevance
“…[21-23, 27-33, 57-73] Elsaesser, Nibbering, and coworkers [27][28][29][30][31][32] have conducted a series of time-resolved IR absorption measurements on the hydrogen-bonding interactions of coumarin 102 (C-102). A very similar dye coumarin 153 (C-153) has been widely used in polar solvation studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[21-23, 27-33, 57-73] Elsaesser, Nibbering, and coworkers [27][28][29][30][31][32] have conducted a series of time-resolved IR absorption measurements on the hydrogen-bonding interactions of coumarin 102 (C-102). A very similar dye coumarin 153 (C-153) has been widely used in polar solvation studies.…”
Section: Discussionmentioning
confidence: 99%
“…In these hydrogen-bonding studies the C-102 molecule was found to act as a base in solution, accepting a hydrogen bond at the C=O site of the coumarin backbone. [31][32] Upon ultrafast electronic excitation the C=O···H bond was cleaved within 200 fs, which indicates that the excited coumarin molecule becomes a weaker base. Elssaeser, Nibbering, and co-workers have concluded the hydrogen-bond breakage is most probably not immediate and that hydrogen-bond dynamics are likely to occur below their time resolution (170 fs) following the electronic excitation of the hydrogen-bond acceptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,[38][39][40][41][42] Excited-state proton-transfer reactions have also been widely studied using 7-aminocoumarins. [43][44][45][46][47][48] We have recently published a theoretical study of coumarins 151 and 120. 49 These coumarins have been used in a variety of applications but are small enough to admit treatment with a wide range of electronic structure techniques.…”
Section: Introductionmentioning
confidence: 99%
“…21 Time-resolved vibrational spectroscopic experiments on the hydrogen bonded complexes of C102 with phenol, 22,23 aniline 24 and water 25 indicated the cleavage of the hydrogen bonds in a few hundred femtoseconds following the S 0 S 1 excitation of C102. Theoretical calculations, however, indicated the initial strengthening of hydrogen bonds in these complexes after the excitation of the dye molecule.…”
mentioning
confidence: 99%